DEVELOPING STUDENT POTENTIAL THROUGH THE ELEMENTARY SCHOOL PROGRAM AT TELUK TIRAM 1 ELEMENTARY SCHOOL BANJARMASIN - Titania Qhaifa Maidah; Ahmad Suriansyah; Arta Mulya Budi Harsono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2026)
Elementary education plays a crucial role in shaping character and developing students' potential. However, school learning practices often focus solely on academic aspects, leading to under-development of students' interests, talents, and creativity. This situation necessitates programs that provide spaces for expression, real-world experiences, and a learning environment that supports the development of individual potential from an early age. To understand the implementation of the elementary school creative program at SDN Teluk Tiram 1 Banjarmasin, this study employed a qualitative exploratory case study design. Data were collected using participatory observation of creative activities, comprehensive interviews with the principal, educators, and students, and document analysis, with the program's implementation at the elementary school level as the unit of analysis. Findings indicate that the program successfully channeled students' diverse talents, from arts and culture to skills, while also enhancing self-confidence, courage to perform, collaboration, and responsibility. A positive impact was also seen in the school community's increased appreciation of student creativity, despite challenges such as weather and limited facilities. The elementary school creative program has been shown to support the development of student potential while strengthening the role of teachers as facilitators of creativity. These findings indicate that a similar model has the potential for broader application as a holistic learning strategy based on local potential.